REFLECTIVE THINKING AND THE TRADITION OF ISLAMIC JURISPRUDENCE - Muhlison Siregar (Journal Analytica Islamica, 2021)
Reflective thinking can occur when a person experiences confusion, obstacles or doubts in solving a problem he faces. Basically, reflective thinking is a person's ability to select the knowledge that has been owned and stored in his memory to solve any problems faced to achieve his goals. The method used to obtain the data needed in this discussion is the Library Research method. The result is that as a source of value, the Koran is strived to continue to be understood and actualized in the daily lives of Muslims. In line with this, humans were created with full limitations. No matter how great a human being, it is not certain that he has actually arrived at the "correct" degree or position in understanding the text (Qur'an) desired by Him. For that reason, human thought must be treated as a human work that cannot be separated from its shortcomings. It is so complex to understand the text (the Qur'an) that a theory is needed in order to capture the enlightenment of Allah SWT in the Qur'an or the Sunnah of the Prophet Muhammad. Along with this, the practice of ijtihad was born.